A cross- sectional study on prevalence of hypertension and its relationship with selected demographic factors in western Uttar Pradesh - Singh, Ranjana; Agarwal, Renu; Singh, Sujan; Gupta, S C (Indian Journal of Community Health, 2014)
Background: Non-communicable diseases (NCDs) are major contributors of morbidity and mortality in the middle aged and elderly population. Aim: The purpose of this study was to estimate the prevalence/distribution of hypertension in persons aged 45 years or above and to find the association with certain selected demographic factors. Materials and Methods: The study used a cross-sectional community based survey of the civilian, non-institutionalized population of Agra district through an in-home interview and a clinical examination (measurement of blood pressure). A total of 544 persons from an urban and rural community were selected by multistage simple random sampling technique. Results: Out of total 544 participants, 47% and 53% were from urban and rural area respectively. Maximum participants were in the age group of 45-54 year (47.43%).The prevalence of hypertension significantly increased with increasing age, being 28.29% in 45-54 year age group to 62.07% in 75+ age group with statistically significant (p<0.001) difference .The overall prevalence of hypertension was found to be 36.42%, which was more common (41.96%) in urban area as compared to rural area (31.46%). Males and females had almost equal (36.49% Vs 35.92%) prevalence of hypertension. The prevalence of hypertension was found to be highest in urban males (40.90%). It was also significantly higher among graduate & above educated group (45.32%). In regard to occupation the hypertension prevalence was lowest among the unskilled laborers (27.27%) and highest among shopkeeper/clerk/teacher/professionals (51.81%) with a significant difference. Majority of the urban participants (50%) were from socioeconomic class I & II, whereas majority from rural background (59.77%) were in socioeconomic class IV & V. The prevalence of hypertension decreased significantly (p<0.01) from` 51.11% in S.E. class-I to 30.25% in class-V. About 17.14% of the retired and unemployed persons were having stage II hypertension. Conclusion: Strategies to detect and treat hypertension in the early stage have to be implemented early.